2021
DOI: 10.1097/md.0000000000026777
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mortality in primary Sjögren syndrome–related interstitial lung disease

Abstract: Aim of the study was to determine the characteristics and prognosis, and to identify the risk factors for mortality in patients with primary Sjögren syndrome (pSS) with interstitial lung disease (pSS-ILD). A total of 1422 patients with SS were screened and 178 patients with pSS-ILD were recruited. The medical records and outcomes were retrospectively reviewed. Overall survival and case control study were performed to explore the predictors of death. Among 178 pSS-ILD patients, 87.1% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Eleven studies had a prospective design, and among them four were conducted in Greece [ 17 , 18 , 19 , 20 ], three in Sweden [ 21 , 22 , 23 ], one in Spain [ 24 ], one in the Netherlands [ 25 ], two in Italy [ 26 , 27 ], and one in China [ 28 ]. Nineteen studies had a retrospective design, and among them ten were conducted in China [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], three in Turkey [ 38 , 39 , 40 ], two in France [ 41 , 42 ], one in Italy [ 26 ], one in the Netherlands [ 43 ], one in Japan [ 44 ], one in Spain [ 45 ], and one in Germany [ 46 ]. Many of them referred to pSS patients fulfilling the revised criteria proposed by the American–European Consensus Group [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies had a prospective design, and among them four were conducted in Greece [ 17 , 18 , 19 , 20 ], three in Sweden [ 21 , 22 , 23 ], one in Spain [ 24 ], one in the Netherlands [ 25 ], two in Italy [ 26 , 27 ], and one in China [ 28 ]. Nineteen studies had a retrospective design, and among them ten were conducted in China [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], three in Turkey [ 38 , 39 , 40 ], two in France [ 41 , 42 ], one in Italy [ 26 ], one in the Netherlands [ 43 ], one in Japan [ 44 ], one in Spain [ 45 ], and one in Germany [ 46 ]. Many of them referred to pSS patients fulfilling the revised criteria proposed by the American–European Consensus Group [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many of them referred to pSS patients fulfilling the revised criteria proposed by the American–European Consensus Group [ 47 ]. In 23 studies out of the 30 included HRCT was performed to investigate lung involvement [ 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The main characteristics of the selected studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Esophageal dilatation, esophageal motor dysfunction also associated with higher prevalence of ILD(66) CTDs, connective tissue diseases; MCTD, mixed connective tissue disease; SLE, systemic lupus erythematosus; SSc, systemic sclerosis; MCTD-ILD, interstitial lung disease in course of mixed connective tissue disease; PFTs, pulmonary function tests; NSIP, non-specific interstitial pneumonia; GGO, ground glass opacity; ILD, interstitial lung disease.…”
mentioning
confidence: 99%
“…Moreover, there was no difference in the frequency of positive autoantibodies such as ANA and anti-SSB between the non-survivors and survivors. The previous study support our findings; Gao et al, in 178 patients with SJS-ILD, reported that the frequency of positive ANA (65.2 vs 75.8%, P = 0.329), anti-SSA (56.0 vs 57.3%, P = 0.907), and anti-SSB (40.0 vs 37.3%, P = 0.812) was not different between the non-survivors and survivors, suggesting that autoantibodies were not associated with prognosis of ILD 44 . However, there is also a contradictory report; Boitiaux et al, in 45 newly diagnosed patients with idiopathic interstitial pneumonia, showed that the anti-SSA (+) group (n = 15) had lower vital capacity (63 ± 22 vs. 87 ± 23% predicted, P = 0.006) and more frequent GGO (87 vs 67%, P = 0.001) and reticulation (33 vs 21%, P = 0.030) on HRCT than the anti-SSA(−) group (n = 30) 45 .…”
Section: Discussionmentioning
confidence: 98%